Hubungan Pengetahuan Perawat Tentang K3 Dengan Kepatuhan Penggunaan Alat Pelindung Diri (APD) di Puskesmas Wirang - Muhammad Arief Wijaksono; Erma Wiliani; Mohammad Basit (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
Occupational Health and Safety (OHS) is a key factor in creating a safe and productive work environment, particularly in healthcare sectors such as Community Health Centers (Puskesmas). Therefore, adequate OHS knowledge is crucial for establishing a safe workplace, preventing occupational accidents, and enhancing the overall quality of healthcare services. This study aims to determine and analyze the relationship between nurses' levels of Occupational Health and Safety (OHS) knowledge and their compliance with the use of Personal Protective Equipment (PPE) at Puskesmas Wirang. A cross-sectional study design was employed. The study was conducted at Puskesmas Wirang with a sample of 15 nurses selected via purposive sampling. Data were collected using a questionnaire. The results indicate that the majority of respondents were aged 36–45 years (66.7%), female (66.7%), had worked for more than 5 years (73.3%), and held a Diploma III (D3) degree in Nursing (60%). The majority demonstrated good OHS knowledge (93.3%) and compliance with PPE usage (86.7%). The study concludes that the majority of nurses at Puskesmas Wirang possess good OHS knowledge and comply with PPE usage protocols.